Climate change litigation and central banks - Joana Setzer; Catherine Higham; Andrew Jackson; Javier Solana (European Central Bank (ECB), 2021)
Given the urgent need to dramatically reduce greenhouse gas emissions, and concern regarding insufficient climate action and ambition across the globe, NGOs and individuals are increasingly turning to the courts to force States, public authorities, and private entities to increase their climate action and ambition and hold them accountable through climate-related litigation. The three contributions in this legal working paper discuss various aspects of such climate change litigation around the world. The papers examine the evolution of climate-related cases, the scope of such cases and the varying grounds on which they have been based. They also focus in some detail on certain key judgments addressing novel issues, as well as a recent climate-related case brought against a national central bank. The papers were originally presented at the Legal Colloquium on "Climate change litigation and central banks - Action for the environment", organised by the European Central Bank on 27 May 2021.
Keywords: K32; K33; K39; K41; Q54; 330; climate-related litigation; climate change; climate risk; financial risk; compilation of cases; Article 11 TFEU; monetary policy; corporate sector purchase programme; litigation against financial institutions; Ireland; European Convention on Human Rights; transnational legal networks; right to an environment; legal standing